[Soukupová, Helena. Svatá Anežka Česká: život a legenda] - Stará, Lenka (Religio, 2016)
Soukupová, Helena. Svatá Anežka Česká: život a legenda. Vyd. 1. Praha: Vyšehrad, 2015. 477 s. ISBN 978-80-7429-471-6.